Fra novice til oldtimer – domsmandsrollen som læringsproces - Louise Victoria Johansen (Nordisk Tidsskrift for Kriminalvidenskab)
Jury systems rest on the notion that not only specialized judges, but also “ordinary” people should judge defendants. Lay judges are supposed to contribute with their mundane, common sense, untouched by legal reasoning and knowledge. These ideals are also prevalent in Denmark. However, Danish lay judges are appointed for a four-year period and may even serve several periods. The present paper analyses how the repeated participation of newly appointed lay judges in Danish criminal cases changes the way they perceive their own role, as well as their perception of what constitutes relevant knowledge in a case. Over time, there is a tendency to learn and apply a way of reasoning that is closer to the court and its codes than it is to their own everyday life. In this way, the nature of their participation as “lay judges” is challenged.